PEMANFAATAN KOLANG KALING DAN BUAH NANAS TERHADAP MUTU SELAI CAMPURAN - SUZANA KHAIRANI; VONNY SETIARIES JOHAN; NOVIAR HARUN (Jurnal Sagu, 2019)
The purpose of this study was to obtain the best percentage of mixed kolang kaling and pineapple fruit tomeet the quality of jam baes on SNI No. 01-3746:2008. This study used experimental method using a completerandomized design (RAL) consisting of five treatments with three replications to obtain fifteen experimentalunits. The treatment of this study was the percentage of kolang kaling porridge and pineapple pulp: KN1(90:10), KN2 (80: 20), KN3 (70: 30%) KN4 (60:40) and KN5 (50:50). Data were analyzed using Analysis ofVariance (ANOVA) and Duncan New Multiple Range Test (DNMRT) at 5% level. The best treatment of thisresearch was KN5 which had moisture content of 26,56%, ash content of 0,49%, crude fiber of 0,85%, totaldissolved solid of 65,20 °brix, sucrose content of 54,74%, viscosity 104421,22 cPs. The results of the sensorytest were descriptively colored of yellow, flavourful of kolang kaling and pineapple fruit, the taste of kolangkaling and pineapple fruit, soft texture and overall assessment hedonic jam was favored by panelists.